2020
DOI: 10.1001/jamanetworkopen.2020.16869
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prehospital Plasma With Survival in Patients With Traumatic Brain Injury

Abstract: IMPORTANCE Prehospital plasma administration improves survival in injured patients at risk for hemorrhagic shock and transported by air ambulance. Traumatic brain injury (TBI) is a leading cause of death following trauma, but few early interventions improve outcomes. OBJECTIVE To assess the association between prehospital plasma and survival in patients with TBI. DESIGN, SETTING, AND PARTICIPANTS The Prehospital Air Medical Plasma (PAMPer) trial was a pragmatic, multicenter, phase 3, cluster randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 47 publications
3
77
0
1
Order By: Relevance
“…Bezüglich der kompromittierten Gerinnung des Traumapatienten zeigte die innerklinische Gabe von Plasma eine verminderte traumaassoziierte Koagulopathie und einen verbesserten pH-Wert [16,17]; auch bei polytraumatisierten Patienten mit Schädel-Hirn-Trauma scheint ein Benefit zu bestehen [18].…”
Section: Diskussionunclassified
“…Bezüglich der kompromittierten Gerinnung des Traumapatienten zeigte die innerklinische Gabe von Plasma eine verminderte traumaassoziierte Koagulopathie und einen verbesserten pH-Wert [16,17]; auch bei polytraumatisierten Patienten mit Schädel-Hirn-Trauma scheint ein Benefit zu bestehen [18].…”
Section: Diskussionunclassified
“…Additionally, transport origin (scene of accident vs. hospital transfer) was used as a proxy for time-to-plasma resuscitation. When grouped by transport origin, patients transported from the scene of the accident who received plasma had lower 30-day mortality than those who did not receive plasma, while there was no difference between patients receiving plasma vs. no plasma when transported from a referral emergency department, suggesting that minimizing time from injury to administration may be important (46).…”
Section: Natural Colloidsmentioning
confidence: 97%
“…Gruen (46) et al reported the secondary analysis of a predefined subgroup of patients with TBI from the PAMPer trial. The PAMPer trial ( 52) was a multi-center, clusterrandomized, phase-3 superiority clinical trial comparing plasma administration to standard-care resuscitation in severely injured patients during air-medical transport, and the primary outcome was mortality at 30 days.…”
Section: Natural Colloidsmentioning
confidence: 99%
“…As these markers were reduced long after the resuscitation had ceased, preservation of the glycocalix seems a likely mechanism of the beneficial effects of prehospital plasma. Of interest, the benefit of prehospital plasma was also shown for the subgroup of TBI patients 32 . Although mechanisms are not clear, benefits of plasma in the specific setting of TBI may not be related to volume expansion but again to a reduction of endothelial dysfunction, 31 which may have contributed to preservation of the blood brain barrier.…”
Section: The Effect Of Plasma On the Endothelial Glycocalixmentioning
confidence: 99%
“…Of interest, the benefit of prehospital plasma was also shown for the subgroup of TBI patients. 32 Although mechanisms are not clear, benefits of plasma in the specific setting of TBI may not be related to volume expansion but again to a reduction of endothelial dysfunction, 31 which may have contributed to preservation of the blood brain barrier. The benefit of plasma may also relate to the duration of shock and hence the severity of endothelial injury, given that plasma may be particularly beneficial in patients with long transport times to the hospital.…”
Section: The Effect Of Plasma On the Endothelial Glycocalixmentioning
confidence: 99%